2008
DOI: 10.1021/ie701704q
|View full text |Cite
|
Sign up to set email alerts
|

Selective Extraction and Identification of Neutral Nitrogen Compounds Contained in Straight-Run Diesel Feed Using Chloride Based Ionic Liquid

Abstract: Extraction of neutral nitrogen-containing compounds (N-compounds) has been investigated with chloride based ionic liquids (ILs) with varying cation classes (imidazolium, pyridinium). ILs were first discriminated by their mutual solubility of ILs and model fuel. Low solubility of 1-butyl-3-methylimidazolinium chloride (BMImCl) and 1-octylpyridinium chloride (OcPyCl) in the model fuel was observed. The ILs were then evaluated using a synthetic solution with dibenzothiophene and carbazole as model compounds, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
54
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 27 publications
2
54
0
Order By: Relevance
“…6 Liquid-liquid extraction (LLE) is an efficient process as compared to distillation, absorption, and other chemical process for the removal of aromatic sulfur and nitrogen containing compounds from diesel oil. [12][13][14] The main advantages of LLE as compared to other separation processes are ambient temperature and atmospheric pressure, 15 no additional catalyst, 15,16 and low energy consumption. 2 In addition, the hydrogen consumption and handling are also eliminated.…”
Section: Introductionmentioning
confidence: 99%
“…6 Liquid-liquid extraction (LLE) is an efficient process as compared to distillation, absorption, and other chemical process for the removal of aromatic sulfur and nitrogen containing compounds from diesel oil. [12][13][14] The main advantages of LLE as compared to other separation processes are ambient temperature and atmospheric pressure, 15 no additional catalyst, 15,16 and low energy consumption. 2 In addition, the hydrogen consumption and handling are also eliminated.…”
Section: Introductionmentioning
confidence: 99%
“…For example, imidazolium-based ILs with HSO 4 -anion or H 2 PO 4 -anion 9-11 achieved very high basic N-extraction efficiency of more than 90 %. Charles et al 12 found that ILs with N(CN) 2 anion exhibited a better extraction effect for non-basic N-compounds than for basic N-compounds, e.g., the extraction efficiency of carbazole can reach 100 % with [BMI] 14,15 has a very highly selective extraction for neutral N-compounds in the diesel oil, while a further study 16 found that the ionic liquid can remove 55 % of nitrogen from straight run gas oil containing 0.0105 w% nitrogen. Gabric et al 17 selected five imidazolium-based ILs to extract thiophene, dibenzothiophene and pyridine from two model solutions, and found the extraction efficiency of pyridine was almost twice higher than that observed for thiophene and dibenzothiophene.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, they have also been widely applied to remove sulfur compounds from fuels through an extraction process. [21][22][23] However, ILs exhibit a limited sulfur extraction ability which can reach a value of ~12-30 %. 24 Interestingly, Zhang et al 25 reported a promising simultaneous extraction and catalytic oxidative desulfurization and denitrogenation system using a functionalized ionic liquid component in a IL/M n Xn (where M: Fe, Zn and n = 2 or 3) system in the presence of a rather simpler oil mixture of two sulfur (100 ppm) and nitrogen (500 ppm) containing substrates.…”
Section: Introductionmentioning
confidence: 99%